Augmented reality in facilitating learning: a review - Azmah Saat,; Nur Izah Ab. Razak,; Razif Abas,; Rahmita Wirza O.K. Rahmat, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The present study reviews the augmented reality application in the education area. Justification of the use is to improve the learning motivation and outcome of students through the use of a deep learning approach. A deep learning approach is associated with better academic performances. Augmented reality provides a tool to motivate learning and understanding in the student. In the medical domain, augmented reality may serve as replacement of cadavers especially during online learning. The main aim of the current review is to reflect the use of augmented reality as a teaching and learning tool to motivate and promote the deep learning approach process which includes life-long learning and possible research areas that warrant and assess the impact of augmented reality on academic performance. Augmented reality may be a tool in complementing the learning aids of the conventional methods of teaching and learning.